Correlating Biodegradation Kinetics of 2,4-Dichlorophenoxyacetic Acid (2,4-D) and 2,4,5-Trichlorophenoxyacetic Acid (2,4,5-T) to the Dynamics of Microbial Communities Originating From Soil in Vietnam Contaminated With Herbicides - Nguyen, Thi Lan Anh; Dang, Ha Thi Cam; Koekkoek, Jacco; Dat, Ton That Huu; Braster, Martin; Brandt, Bernd W.; Parsons, John R.; Brouwer, Abraham; van Spanning, Rob J. M. (Frontiers in Sustainable Cities, 2021)
We determined the degradation rates of the herbicides 2,4-D and 2,4,5-T by 2 different bacterial communities. One of these originated from soil heavily contaminated with herbicides from Bien Hoa airbase, the other from the same soil but amended with additional carbon and energy sources. The community from the contaminated, but untreated, soil degraded both 2,4-D and 2,4,5-T within 5 days of cultivation. The one from the amended soil, however, hardly showed any degradation of the compounds throughout 23 days of cultivation. After refreshment of the medium and prolonged culturing, however, this community degraded both herbicides within 25 days with progressively increasing rates. nMDS analysis revealed a highly significant differentiation pattern of the 2 communities. Cultures inoculated with amended soil showed a significant increase of Bacillus and Paenibacillus upon prolonged exposure to the herbicides. The succession in the culture from untreated soil, on the other hand, was dominated by species from the Proteobacteria. We were able to isolate 2 of them and they were shown to be related to Bordetella petrii and Sphingomonas histidinilytica, successively. Subsequent PCR analyses of their DNA revealed the presence of key genes involved in the degradation of the herbicides. This study provides a more fundamental understanding of the biodegradation of 2,4-D and 2,4,5-T by displaying the bacterial community succession during their breakdown allowing a comprehensive view on potential key degraders.